1993
DOI: 10.1128/mcb.13.4.2623
|View full text |Cite
|
Sign up to set email alerts
|

A complex regulatory element from the yeast gene ENO2 modulates GCR1-dependent transcriptional activation.

Abstract: The GCR1 gene product is required for maximal transcription of many yeast genes including genes encoding glycolytic enzymes. Transcription of the yeast enolase gene EN02 is reduced 50-fold in strains carrying a gcrl null mutation. cis-acting sequences that are sufficient for GCRI-dependent regulation ofEN02 expression were identified by using an enhancerless CYC1 promoter which is not normally dependent on GCR1 for expression. A 60-bp EN02 sequence that was sufficient to provide high-level, GCRI-dependent tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

1994
1994
2004
2004

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 68 publications
1
27
0
Order By: Relevance
“…The RAP1 binding site in the gastrin promoter is adjacent to cis-regulatory elements which bind transcriptional repressors (ATTCCTCT) or activators (CATATGG). This is consistent with previous studies in yeast suggesting that the regulatory function of RAP1 is determined by the context of its binding site and, presumably its interaction with other factors [36,37]. Gel mobility shift assays and methylation interference studies also demonstrated sequence specific DNA-protein interactions between the gastrin DNA element and recombinant RAP1 protein identical to those reported for RAP1 binding sites in yeast promoters.…”
Section: Discussionsupporting
confidence: 79%
“…The RAP1 binding site in the gastrin promoter is adjacent to cis-regulatory elements which bind transcriptional repressors (ATTCCTCT) or activators (CATATGG). This is consistent with previous studies in yeast suggesting that the regulatory function of RAP1 is determined by the context of its binding site and, presumably its interaction with other factors [36,37]. Gel mobility shift assays and methylation interference studies also demonstrated sequence specific DNA-protein interactions between the gastrin DNA element and recombinant RAP1 protein identical to those reported for RAP1 binding sites in yeast promoters.…”
Section: Discussionsupporting
confidence: 79%
“…For quantitation of RP026 mRNA, the amount of signal generated from both mutant and wild-type initiation sites (indicated by brackets) were quantitated for lanes 2 to 4. for the ADHl gene amongst different wild-type yeast strains (Bennetzen and Hall, 1982;Pinto et al, 1992Pinto et al, , 1994. The role of Abflp binding-sites in the expression of a variety of genes has been studied (Buchman and Kornberg, 1990;Della Seta et al, 1990a,b;Dequard-Chablat et al, 1991;Halfter et al, 1989;Hamil et al, 1988;Herruer et al, 1989;Kraakman et al, 1991;Mager and Planta, 1990;Sinclair et al, 1994;Trawick et al, 1992;Willett et al, 1993); however, to our knowledge, this is the first report of a shift in the initiation sites of transcription due to a mutation in an Abflp binding-site. In other studies, promoters have often been used to drive expression of the lacZ reporter gene and the effects of Abfl p binding-site mutations have been analysed by monitoring b-galactosidase activity in cellular extracts.…”
Section: Role Of Abflp In Thh Expression Of Rp026 New Transcription-imentioning
confidence: 94%
“…For these genes Abflp appears to facilitate the access of other regulatory factors to promoters, thereby mediating their regulatory effects (GonCalves et al, 1995;Trawick et al, 1992;Willett et al, 1993). The ability of Abflp to create a sharp bend in DNA (McBroom and Sadowski, 1994) and to position nucleosomes on the promoter (De Winde et al, 1993) might underlie the mechanism by which it facilitates access to DNA for other regulatory factors.…”
Section: Role Of Abflp In Thh Expression Of Rp026 New Transcription-imentioning
confidence: 99%
See 2 more Smart Citations